The Uniting Innovation and Stability: The Key to Business Flexibility - Gatot Wijayanto; Arini Novandalina; Yutiandry Rivai; Jushermi (Ambidextrous Journal of Innovation Efficiency and Technology in Organization, 2023)
This study investigates the interconnectedness between Level of Business Innovation (LBI), Financial Stability (FS), Industry Competition Level (LIC), and Business Flexibility (BF). Utilizing Smart-PLS analysis, direct effects were affirmed, showing LBI's positive impact on LIC and BF, FS's influence on LIC, BF, and LIC's effect on BF. Additionally, indirect effects were examined, revealing LBI and FS indirectly affecting BF through LIC mediation. Results demonstrate that heightened Business Innovation fosters Industry Competition and Business Flexibility. Improved Financial Stability correlates with heightened Industry Competition, thereby impacting Business Flexibility. However, indirect impacts from LBI and FS to BF via LIC were modest but statistically significant, highlighting the mediated influence of Industry Competition. Understanding these relationships illuminates strategies leveraging innovation, stability, and industry competition for organizational adaptability. The study underscores the complexity of these linkages, guiding businesses toward enhancing adaptability and resilience in competitive markets.